Predictive factors for response to Lamivudine in chronic hepatitis B - Luiz Caetano da SILVA; Luís Edmundo Pinto da FONSECA; Flair José CARRILHO; Venâncio Avancini Ferreira ALVES; Roberta SITNIK; João Renato Rebello PINHO (Universidade de São Paulo (USP), 2000)
BACKGROUND: Lamivudine has been shown to be an efficient drug for chronic hepatitis B (CHB) treatment. AIM: To investigate predictive factors of response, using a quantitative method with high sensitivity. METHODS: We carried out a prospective trial of lamivudine in 35 patients with CHB and evidence for viral replication, regardless to their HBeAg status. Lamivudine was given for 12 months at 300 mg daily and 150 mg thereafter. Response was considered when DNA was undetectable by PCR after 6 months of treatment. Viral replication was monitored by end-point dilution PCR. Mutation associated with resistance to lamivudine was detected by DNA sequencing in non-responder patients. RESULTS: Response was observed in 23/35 patients (65.7%) but only in 5/15 (33.3%) HBeAg positive patients. Only three pre-treatment variables were associated to low response: HBeAg (p = 0.006), high viral load (DNA-VHB > 3 x 10(6) copies/ml) (p = 0.004) and liver HBcAg (p = 0.0028). YMDD mutations were detected in 7/11 non-responder patients. CONCLUSIONS: HBeAg positive patients with high viral load show a high risk for developing drug resistance. On the other hand, HBeAg negative patients show a good response to lamivudine even with high viremia.